Construtivismo de marco teórico-pedagógico a grife: um estudo a partir das mensagens veiculadas na internet - Silva, Cleania de Sales (2012)
This thesis is resulted of a research on propagated the social representations of constructivism in the Internet, which as had estimated basic the idea of Moscovici (1961) of that the media it has determinative paper in the popularization of the scientific theories, in formation e propagation of the social representations and in the construction of behaviors human beings. Understanding the Internet as latest space of circulation of social communications, therefore, privileged field (and still not explored) for studies of social representations, we choose this half midiático as investigative field of our research, it if it constitutes in the "great ocean of the new informational planet" (LEVY, 2000, p. 126), besides making possible the interaction with different forms of images, different individuals, different ' world ', configuring itself as important space of symbolic production e of analysis of the representational process in the world contemporary. Based in these questions, we trace as objective to analyze the circulating speech propagated on-line on the constructivism, searching to apprehend the social representations shared the respect. This objective was constructed in face of the insertion of the theory constructivist in the educational way has two decades more than, as well as of its consolidation as reference in different social contexts, mainly in midiático. The question that directed the research was: as this theory obtains to penetrate in some layers of our society, to influence the world readings e the behaviors of different people? That modifications it suffers in this trajectory and which the paper of the Internet in this process? The corpus of the research was constituted of the substances on the theory found in the Internet, in pages in Portuguese of Google, in the period of 27 of July of 2004 the 17 of August of 2004. The data they had been analyzed on the basis of the project of analysis of content elaborated for Moscovici (1961) and in the estimated theoreticians of the social communication, in special of the hypermedia. The results had disclosed that the Internet participates of determinative form in the process of popularization of the constructivism theory, not only spreading out its estimated theoretician- methodological for the domain public (diffusion), but propagating positive beliefs and images of its postulates (propagation) and using them it service of interests politicians e financiers (propaganda). The popularization of the constructivism in the Internet and social representations of this theory propagated configure one process in which the theory passes of pedagogical theoretical landmark for grief, assuming a commercial character extremely and the status of solution for problems of the education and the society, stirring up attitudes and behaviors in public, most general possible, that comes to take care of to the interests politicians e marketing. Recognizing the diversity, the permanent renewal of information and the negotiation of directions gifts in the Internet, as well as the innumerable ones forms of access to the information found by it, we consider results of the research as fruits of the inherent characteristics to this way midiático, to the time where we call the attention for relativity these results, for the plasticity of knowing them and sensible propagated on-line e for the great challenge that the hypermedia imposes to the study of communication phenomena, of the social representations and in educational quarrels and for the necessity of new research that they investigate the forms of socialization of the information and communication propitiated by hypermedia and its implications in the construction of the symbolic universes and in practical social